2002
DOI: 10.1080/0305724022000008115
|View full text |Cite
|
Sign up to set email alerts
|

The Defining Issues Test and the Four Component Model: Contributions to professional education

Abstract: This article reviews studies examining the effect of professional education on ethical development. Most studies limit assessment to the measurement of moral judgement, observing that moral judgement plateaus during professional school unless an ethics intervention is present. Whereas interventions influence the shift to postconventional reasoning (the DIT P score), a more illuminating picture of change may emerge if researchers examined DIT profiles. More importantly, limiting assessment to measures of moral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
219
0
16

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 259 publications
(248 citation statements)
references
References 47 publications
6
219
0
16
Order By: Relevance
“…U oblasti proučavanja moralnog mišljenja, stupnjevi koje je predložio Kolberg duže vremena smatrani su aktivnim šemama koje pomažu pojedincu da definiše važne društvene ili moralne aspekte situacije i da identifikuje odgovarajuće procedure postupanja (Bebeau, 2002;Rest, 1974;1975;1994;Rest, et al, 1999). Stupanj moralnog rasuđivanja koji pojedinac dostiže u razvoju važna je i korisna informacija, ali nije sveobuhvatan indikator o tome kako taj pojedinac razmišlja o moralnim pitanjima ili kako prevodi svoje misli u ponašanje (Rest & Narvaez, 1998;prema Lewis, 2007).…”
Section: Uvođenje Posrednih Koncepata U Oblasti Moralnog Mišljenjaunclassified
See 1 more Smart Citation
“…U oblasti proučavanja moralnog mišljenja, stupnjevi koje je predložio Kolberg duže vremena smatrani su aktivnim šemama koje pomažu pojedincu da definiše važne društvene ili moralne aspekte situacije i da identifikuje odgovarajuće procedure postupanja (Bebeau, 2002;Rest, 1974;1975;1994;Rest, et al, 1999). Stupanj moralnog rasuđivanja koji pojedinac dostiže u razvoju važna je i korisna informacija, ali nije sveobuhvatan indikator o tome kako taj pojedinac razmišlja o moralnim pitanjima ili kako prevodi svoje misli u ponašanje (Rest & Narvaez, 1998;prema Lewis, 2007).…”
Section: Uvođenje Posrednih Koncepata U Oblasti Moralnog Mišljenjaunclassified
“…Stupanj moralnog rasuđivanja koji pojedinac dostiže u razvoju važna je i korisna informacija, ali nije sveobuhvatan indikator o tome kako taj pojedinac razmišlja o moralnim pitanjima ili kako prevodi svoje misli u ponašanje (Rest & Narvaez, 1998;prema Lewis, 2007). Novije studije pokazuju da su moralne šeme samo jedan od mnogih sistema koje pojedinac koristi u moralnom domenu (Bebeau, 2002;Thoma, 2006;Thoma, Bebeau & Boland, 2008).…”
Section: Uvođenje Posrednih Koncepata U Oblasti Moralnog Mišljenjaunclassified
“…11 This second component in the FCM, ethical judgment, has been widely studied in nursing and other disciplines. 11 The thoughtful, deliberative nature of ethical reasoning has been compared to the research process, because judgment should reflect knowledge of ethical principles, theories, and professional codes. Unlike in the scientific process, however, the goal is not to achieve certainty but to make a choice that is reasonable and prudent and integrates emotional responses.…”
Section: Ethical Judgmentmentioning
confidence: 99%
“…For example, a review of previous studies of cognitive ethical reasoning across different professions and occupations (Thorne 2000;Borenstein et al 2006;Spring 2004;Bebeau 2002;Loviscky, Trevino & Jacobs 2007) has revealed that the ethical reasoning of financial planners and compliance officers in an Australian context has not been addressed in the existing literature leading to a gap in knowledge in this area.…”
Section: The Gaps In Previous Studiesmentioning
confidence: 99%
“…The DIT and DIT2 instruments have been validated and used in numerous studies (Borenstein et al 2006;Bebeau 2002). Whilst the DIT and DIT 2 instruments have limitations, they have been extensively tested over time and are justified on the empirical literature (Borenstein et al 2006).…”
Section: Measuring Cognitive Ethical Reasoningmentioning
confidence: 99%